JUMLAH MIKROBA DAN SIFAT ORGANOLEPTIK DAGING AYAM BROILER YANG DIRENDAM AIR PERASAN KUNYIT (Curcuma domestica VAL) DENGAN LAMA PENYIMPANAN YANG BERBEDA - Achmad Jaelani; Neni Widaningsih; Selamet Hariadi (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2018)
The purpose of this study was to study and analyze the amount of microbial chicken meat after soaked in turmeric juice (Curcum domestica Val) with different storage period at room temperature. A total of 1 kg of broiler chicken and turmeric juice 7% is used in this study. With a Completely Randomized Design (RAL) step, five treatments and four replications with each replication amounting to one sample. The number of samples used are as many as 40 samples with 20 samples for testing the number of microbes and 20 other samples for organoleptic testing of color, smell and texture of broiler chicken meat. The treatment performed on the sample was K0 = broiler meat without treatment, K3 = broiler chicken storage for 3 hours, K6 = broiler chicken storage for 6 hours, K9 = broiler chicken storage for 9 hours, K12 = broiler chicken storage for 12 hours. The results showed that the storage of broiler chicken meat at room temperature and has been soaked for 30 minutes on the best turmeric juice 7% is the storage for 3 hours, while the organoleptic test can increase the level of fondness in the smell of meat.